Whole-mount imaging of the mouse hindlimb vasculature using the lipophilic carbocyanine dye DiI - Boden, Jeffrey (Biotechniques, 2012)
The availability of transgenic disease backgrounds and the accessibility of molecular research reagents have contributed to make the mouse ischemic hindlimb the model of choice for many studies of angiogenesis, and to investigate new treatments for peripheral artery disease. A limitation of these models involves our inability to easily visualize the regenerated vascular architecture. Approaches such as micro-computed tomography and micro-angiography are expensive, technically demanding and not available to many laboratories. Here we describe a rapid and inexpensive adaptation of a vascular staining procedure for precise imaging of the mouse hindlimb vasculature. We introduced two technical modifications and an analytical extension to the original method including (i) pre-skinning of the muscle prior to fixation that preserves tissue integrity, (ii) mild pressure-desiccation subsequent to fixing that enhances resolution and image penetration, and (iii) reconstruction of confocal data into 3D images. The procedure provides resolution that is equivalent or superior to other approaches at a fraction of the cost, time and technology required.